Polarity-switching top coats enable orientation of sub-10-nm block copolymer domains - Bates, Christopher M; Seshimo, Takehiro; Maher, Michael J; Durand, William J; Cushen, Julia D; Dean, Leon M; Blachut, Gregory; Ellison, Christopher J; Willson, C Grant (Science (American Association for the Advancement of Science), 2012)
Block copolymers (BCPs) must necessarily have high interaction parameters (χ), a fundamental measure of block incompatibility, to self-assemble into sub-10-nanometer features. Unfortunately, a high χ often results from blocks that have disparate interfacial energies, which makes the formation of useful thin-film domain orientations challenging. To mitigate interfacial forces, polymers composed of maleic anhydride and two other components have been designed as top coats that can be spin-coated from basic aqueous solution in the ring-opened, acid salt form. When baked, the anhydride reforms and switches polarity to create a neutral layer enabling BCP feature alignment not possible by thermal annealing alone. Top coats were applied to the lamella-forming block copolymers poly(styrene-block-trimethylsilylstyrene-block-styrene) and poly(trimethylsilylstyrene-block-lactide), which were thermally annealed to produce perpendicular features with linewidths of 15 and 9 nanometers, respectively.